THE EFFECT OF POLITICAL CONNECTIONS AND CORPORATE SOCIAL RESPONSIBILITY ON THE QUALITY OF FINANCIAL REPORTS - Roidwan Elang Sudrajat; Susanti Susanti; Lia Uzliawati (Dynamic Management Journal, 2023)
This study aims to investigate the effects of political connections and disclosure of Corporate social responsibility (CSR) on the quality of financial reports, which are measured using discretionary accruals (DAC). Secondary data obtained from literature studies were used in this study, and the approach used was a qualitative descriptive method. The results show that political connections have a negative impact on the quality of financial reporting, while CSR disclosure has a positive impact on the quality of financial reporting. The stronger the political connections within a company, the more likely the quality of the resulting financial reports will decrease due to conflicts of interest that may occur. On the other hand, the higher the level of CSR disclosure in a company, the better the quality of the financial reports produced, which in turn can increase public trust, especially investors. Keywords: Quality of Financial Reports, Political Connections and Corporate Social Responsibility.